Critical Digital Literacy as a Response to Algorithmic Misinformation - Bambang Iswanto; Adi Saputra; Meli Saraswati (ESENSI: Jurnal Riset Pendidikan, 2026)
The rapid expansion of algorithmically driven digital platforms has transformed how information is produced, distributed, and consumed, while intensifying the spread of misinformation. This study examines critical digital literacy as a strategic educational response to algorithmic misinformation, emphasizing that misinformation is not only a content issue but also a systemic outcome of algorithmic curation, datafication, and platform economies. Drawing on interdisciplinary perspectives from media studies, information literacy, education, and critical theory, this research conceptualizes critical digital literacy as a multidimensional framework integrating algorithmic literacy, critical evaluation of information, ethical awareness, and civic engagement. Using a qualitative interpretive design, the study synthesizes theoretical models and prior empirical findings to analyze how algorithmic systems shape users’ epistemic environments and influence perceptions of credibility, authority, and truth. The findings show that conventional media literacy approaches are insufficient, as they often overlook structural biases, power relations, and the political economy of digital platforms. In contrast, critical digital literacy enables learners to interrogate algorithmic authority, recognize systemic inequalities, and develop reflective agency. The study argues that embedding critical digital literacy in education is essential to build resilience against misinformation and support informed, democratic participation in digital environments.